Three-year caregiver's reports on driving performance: A divination or diagnostic tool for fitness to drive in Parkinson Disease patients - Lee, Hoe (Scientific Research Publishing, Inc., 2013)
Objectives: This study aims to examine whether information provided by spouse or relatives can be employed to identify PD patients with deteriorated driving performance, using three-year care- giver’s reports on their driving ability as the out- come measure. Methods: Fifty-three idiopathic PD subjects were assessed on open roads. Prior to the driving assessment, participants were examined by a geriatrician with various clinical assessments. The caregivers filled out a questionnaire, the scores of which is a reflection of their concern on driving performance of their PD relatives. The same measurements were collected for the subsequent two years. Hierarchical Poisson regression analysis, adjusting for gender, age and driving exposure (hours of driving per week), was then undertaken to determine whether the measures of driving assessment were associated with the score of the questionnaire. Results: During the three-year period, all PD participants were rated at least 3 questions positive in the caregiver’s questionnaire; the worst participant was rated positive eight times. Except the assessment criteria to gauge the traffic rules and regulations compliance, all other measures of the driving assessment were found to be significantly associated with the information provided by the caregivers. Conclusions: This study demonstrated that the in- formation provided by caregivers was useful to identify PD patients with deteriorated driving performance. If adopted as part of the off-road driving assessment for PD patients, the questionnaire can provide reliable information to clinicians.